2012
DOI: 10.1007/s11302-012-9299-2
|View full text |Cite
|
Sign up to set email alerts
|

Anti-inflammatory effects of purine nucleosides, adenosine and inosine, in a mouse model of pleurisy: evidence for the role of adenosine A2 receptors

Abstract: Adenosine and its metabolite, inosine, have been described as molecules that participate in regulation of inflammatory response. The aim of this study was to investigate the effect of adenosine and inosine in a mouse model of carrageenan-induced pleurisy as well as the participation of adenosine receptors in this response. Injection of carrageenan into the pleural cavity induced an acute inflammatory response characterized by leukocyte migration, pleural exudation, and increased release of interleukin-1β and t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
50
0
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 64 publications
(57 citation statements)
references
References 55 publications
(77 reference statements)
3
50
0
2
Order By: Relevance
“…In addition, an inosine analogue (INO-2002) demonstrated similar anti-inflammatory properties in an acute respiratory distress syndrome model [22]. In agreement, a recent study from our group have revealed that inosine significantly reduces pleural acute inflammation, reducing pleural leakage, neutrophil count, TNF-α and IL-1β levels in pleural exudates, an effect dependent on A 2A adenosine receptor activation [23]. Because inosine exerts regulatory effects on immune response [5] and increased tissue inosine levels are quantified in the inflamed sites [4,32], our data suggest that purines constitute a target pathway for the control of allergic asthma.…”
Section: Discussionsupporting
confidence: 76%
See 2 more Smart Citations
“…In addition, an inosine analogue (INO-2002) demonstrated similar anti-inflammatory properties in an acute respiratory distress syndrome model [22]. In agreement, a recent study from our group have revealed that inosine significantly reduces pleural acute inflammation, reducing pleural leakage, neutrophil count, TNF-α and IL-1β levels in pleural exudates, an effect dependent on A 2A adenosine receptor activation [23]. Because inosine exerts regulatory effects on immune response [5] and increased tissue inosine levels are quantified in the inflamed sites [4,32], our data suggest that purines constitute a target pathway for the control of allergic asthma.…”
Section: Discussionsupporting
confidence: 76%
“…Despite all that is known about the effects of inosine, the mechanisms underlying its role in controlling the lung repercussions of allergic inflammation are still unknown. Recent data obtained from our group showed that inosine reduced carrageenan-induced acute pleural inflammation, an effect that involves A 2A and A 2B adenosine receptors [23]. Accordingly, literature data indicates that the activation of A 2 adenosine receptors subtypes is related with downregulation of inflammation and immune responses [4,24,25].…”
Section: Introductionmentioning
confidence: 86%
See 1 more Smart Citation
“…However, more detailed studies are necessary to reveal this novel possibility. In addition, the anti-inflammatory effects of not only Ado [197,198,201,424] but also of Urd and Ino have been demonstrated [403,[424][425][426]; thus, investigation of the effect of Urd and Ino on inflammationinduced exacerbation of epileptic activity [192,193] may also be an interesting and promising novel drug discovery target in epilepsy research.…”
Section: New Developmentsmentioning
confidence: 99%
“…By analogy to the cAMP-adenosine-adenine system (Jackson and Raghvendra 2004), extracellular cIMP may then be hydrolyzed to inosine and hypoxanthine. Inosine and hypoxanthine, in turn, could exert biological effects via adenosine or adenine receptors, respectively (Schiedel et al 2007;da Rocha Lapa et al 2012). These two mechanisms of action of cIMP were not addressed in the study by Chen et al (2014).…”
mentioning
confidence: 99%